‘I Feel Persecuted. It’s So Distressing and Upsetting, It Is All Too Much’. A Disablist Hate Crime Typology: Intimidation, Exploitation and Brutalization - Houghton, Valerie (The British journal of criminology, 2025)
In this article, we develop a typology of disablist hate crime that does justice to the lived experience of victims and highlights the differences between disablist hate crime and other forms of hate crime in England. This research consists of analyses of cases and semi-structured interviews with professionals. Based on interaction type, its duration, meaning, frequency, severity, and harm, we developed three categories: (1) intimidation, (2) exploitation and (3) brutalization. We argue that because of the specific symbolic nature of targeting disabled people, these acts should be considered as potential hate crimes.